ჰეროდოტე – ცნობები კავკასიის შესახებ - გარდაფხაძე ქეთევან (ლოგოსი, 2023)
The article aims to analyze several passages from Herodotus that deal with the origins of Colchis, mention both Aea and Colchis and refer to the ethnos of the Saspeires. This information causes scholarly debates even nowadays. Herodotus, whose works are among the earliest sources referring to the Caucasus, was the first to outline a clear concept of Caucasus and offer almost all basic versions of the terms referring to it (ὁ Καύκασος (I 203, 204): the name of the Caucasus, the name of the Caucasian mountain chain Καύκασις (III, 97), as well as Καυκᾶσιον ὂρος (I 104). The article draws on contemporary research findings related to Herodotus’ information and foregrounds the role of Greek historiography in the study of ancient Caucasus. Based on a number of sources, it can be argued that Aegean-Caucasian encounters can be traced back to the 14th-12th centuries BC, when one part of the Sea Peoples reached the Caucasus and assimilated with the local Colchian population, which is clearly suggested by linguistic as well as archeological evidence. The parallel mention of Aea and Colchis by the Greek historiographer must indicate two, old and new versions of the same place name. Herodotus’ information about the Saspeires can be qualified as the earliest information about the settlement area of Georgians, while linguistic analysis suggests that the major part of the tribes settling the territory of Georgia spoke a Kartvelian language.